EFFECT ON DIETARY PROTEIN AND FEEDING RATE ON GROWTH OF TIGER GROUPER (Epinephelus fuscoguttatus) JUVENILE - Muhammad Marzuqi; Ni Wayan Widya Astuti; Ketut Suwirya (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
The grouper fish culture was developed after its succesful seed production in hatchery well known. In grow-out culture grouper, the protein requirement and feeding rate have to know well in order to understand the effectiveness on feed utilization . The experiment was designed by factorial design with the first factor as 3 dietary protein (36%, 42%, 48%) and the second factor as 3 feeding rate ( 1,5%, 2,0%, 2,5%). Ten of juvenile tiger grouper (102, 51-102, 73 g of body weight) were stocked in 27 polycarbonate tanks with 400 l volume each. Each tank was equiped with aeration and flow-through water system. Fish was fed three time per day i.e. 08:00, 11:30 and 15:30 Central Indonesia Standard Time for 16 weeks. Every week was measured body weight, survival rate, and feed quantity. The parameter used in this experiment were weight gain, spesific growth rate, feed efficiency and survival rate. The results of the experiment showed that the combination of protein level (36%, 42%, 48%) with feed ratio (1.5%, 2.0%, 2.5%) gave response on growth, weight gain and survival rate. Combination dietary protein level of 48% and feed ratio 1.5% gave higher weight gain and survival rate with values of 104.05 ± 5.89% and 96.67 ± 5.57 %, respectively.Keywords: Dietary protein and feeding rate , growth, tiger grouper (Epinephelus fuscoguttatus)